2018
DOI: 10.1515/abm-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bioaerosols in tuberculosis high-risk areas of health care facilities in central Thailand

Abstract: Background Long-term surveillance of airborne bioaerosols in health care facilities is required to protect the health of patients and health care workers. Feasible methods to measure airborne bioaerosol concentrations and determine associated environmental factors may help to avoid nosocomial tuberculosis (TB). Objectives To describe the concentrations and size of airborne bioaerosols and to identify the potential contributors to indoor airborne bioaerosols in TB high-risk areas in health care facilities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, the type of air conditioner used was considered crucial as central air conditioners proved to be more effective than non-centrally sited systems such as window, or single-split types [ 35 , 36 ]. Notably, one study identified that, compared with hybrid ventilation, the concentration of indoor bioaerosols was positively correlated with the type of ventilation system used (e.g., central air conditioners, P < 0.05) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the type of air conditioner used was considered crucial as central air conditioners proved to be more effective than non-centrally sited systems such as window, or single-split types [ 35 , 36 ]. Notably, one study identified that, compared with hybrid ventilation, the concentration of indoor bioaerosols was positively correlated with the type of ventilation system used (e.g., central air conditioners, P < 0.05) [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The contribution by Sornboot et al in the present issue of Asian Biomedicine describes the situation of bioaerosol concentrations in 7 large health care facilities [7]. The authors have documented that it is imperative to improve indoor air quality.…”
mentioning
confidence: 99%